Evaluation of the preventive effect of dexpanthenol in radiation injury by lung perfusion scintigraphy: a preclinical experimental model of radiation injury - Koc, Zehra P.; In, Erdal; Karslioglu, Ihsan; Ucer, Ozlem; Canpolat, Sinan (Lippincott Williams & Wilkins, 2015)
Aim The aim of this study was to show the preventative effects of dexpanthenol in radiation injuries caused by radiotherapy (RT) through the use of lung perfusion scintigraphy in the pre-RT and post-RT periods. Materials and methods Six male New Zealand rabbits (5-6 months of age and approximate to 2.5-3kg in weight) were the used in this study. The animals were subjected to Tc-99m-macroaggregated albumin lung perfusion scintigraphy in the pre-RT and post-RT (i.e. 2 weeks after treatment) periods. The scintigraphies were performed with the same dose by the same staff and the methodology used the same acquisition parameters. The rabbits were divided into two groups: group I (administered RT only) and group II (also administered intramuscular 500mg dexpanthenol injections for 14 consecutive days after RT). Quantification was performed to compare the groups and the quantification variables were compared using a paired samples t-test, with P value less than 0.05 considered to be statistically significant. Histopathological analysis was also carried out. Results The post-RT scintigraphies indicated a decrease in the counts in both lungs, suggesting early post-RT injury. The difference between the counts obtained from both lungs in groups I and II was significantly different and favoured group II. Histopathological results confirmed the scintigraphy results. Conclusion It is possible to estimate post-RT changes in the early period (in contrast to previous data) by lung perfusion scintigraphy. Dexpanthenol may also reduce the effects of RT to a degree. Although this is the first study to report the preventive effects of dexpanthenol on RT injuries, further studies are warranted in this area. Copyright (C) 2015 Wolters Kluwer Health, Inc. All rights reserved.
Keywords: dexpanthenol; perfusion scintigraphy; radiation injury